Nuevas tecnologías y su incidencia en la salud mental de los adolescentes - Giraldo Caro, Paula Andrea (2023)
The vertiginous advance of digital an technological tools has led to a significant impact on humanity, especially, in the adolecent population generating new behavioral patterns and a need for constant updating that ensures permanence in them. The main objective of this research is to identify the incidences of new technologies in the mental health of adolescents by means of a bibliographic review. The methodology used in this research was the documentary review carried out in various databases such as: Dialnet, Scopus, ProQuest, Redalyc, Ebsco Host and academic google. The inclusion criteria used were Adolescence, mental health, new technologies, articles in Spanish and English, countries such as the United States, Spain, Japan and Colombia, and scientific articles published from 2010 to 2020. The exclusion criteria were Population older than 18 years, research articles in Portuguese and less than 2010. The results found in the 30 articles consulted are: Adolescents who use new technologies more frequently, require the development of maladaptive behaviors associated with disorders such as anxiety and depression. However, some adolescents use time in these new technologies to study and create interpersonal relationships through virtual communities. It is concluded that there is a correlation between the time spent on new technologies and the incidences in adolescent mental health, and, despite having found positive incidences, many of the incidences found are negative.